Mechanical regulation of calcium signaling of HL-60 on P-selectin under flow. Issue 2 (December 2016) - Huang, Bing; Ling, Yingchen; Lin, Jiangguo; Fang, Ying; Wu, Jianhua
Abstract Background Binding of P-selectin to P-selectin glycoprotein ligand-1 (PSGL-1) makes neutrophils roll on and adhere to inflammatory site. Intracellular calcium bursting of adhered neutrophils is a key event for subsequent arresting firmly at and migrating into the injured tissue. But, it remains unclear how the cytoplasmic calcium signaling of the cells were modulated by the fluid shear stress. Here, we focus on mechanical regulation of P-selectin-induced calcium signaling of neutrophil-like HL-60 cells under flow. Methods HL-60 cells were loaded with Fluo-4 AM for fluorescent detection of intracellular calcium ion, and then perfused over P-selectin-coated bottom of parallel-plate flow chamber. The intracellular calcium concentration of firmly adhered cell under flow was observed in real time by fluorescence microscopy. Results Force triggered, enhanced and quickened cytoplasmic calcium bursting of HL-60 on P-selectin. This force-dependent calcium signaling was induced by the immobilized P-selectin coated on substrates in absence of chemokine. Increasing of both shear stress and P-selectin concentration made the calcium signaling intensive, through quickening the cytosolic calcium release and upregulating both probability and peak level of calcium signaling. Conclusions Immobilized P-selectin-induced calcium signaling of HL-60 cells is P-selectin concentration- and mechanical force-dependent. The higher both the P-selectin concentration and the external force on cell, the more intensive the calcium signaling. It might provide a novel insight into the mechano-chemical regulation mechanism for intracellular signaling pathways induced by adhesion molecules.